Printing of PEDOT:PSS for top gate organic thin film transistor. Issue 1 (January 2021) - Darwis, D; Sesa, E; Elkington, D; Sharafutdinova, G; Lewis, T; Zhou, X; Dastoor, P C.; Belcher, W J.
Abstract: This report present a thorough discussion of the DOD inkjet printing technology, including technical skills and information about Dimatix inkjet printer employed for the realisation of devices. The use of inkjet printing for the deposition of the conducting polymer PEDOT:PSS was successfully demonstrated for top gate electrode organic thin film transistors. This investigation offers a significant contribution in order to the efficient fabrication of OTFTs.